IDENTIFIKASI KARAKTER MORFOLOGIS SALAK SUMATERA UTARA (Salacca sumatrana Becc.)DI BEBERAPA DAERAH KABUPATEN TAPANULI SELATAN - Hilda Mei Yeni Harahap; Eva Sartini Bayu; Luthfi A. Mahmud Siregar (Jurnal Agroekoteknologi, 2013)
The objective of the research was to identify morphological characters and phylogenetic relationship among Salacca sumatrana at South Tapanuli Region. The study conducted in June to August 2012 at Sibio-bio Angkola Timur, South Tapanuli (+ 1100 m asl),  Siamporik Angkola Selatan (+ 900-1100 m asl) , and Parsalakan Angkola Barat (+ 1200  m asl). The method to use descriptive method, purposive sampling method and than cluster method to see relationship Sumatra salak at South Tapanuli. The results obtained from the three villages were simililarity morphological characters such as caulis form, folium form, folium color, vagina color, spina color, flos malculus color and hermafroditus and sphata color. From phylogenetic relationship                Salacca sumatrana in three villages Tapanuli Selatan the similarity is 63,77% which grouped into 2 groups. That higest similarity from village Parsalakan sampel C6 with C9equal to 98,65%,, while that lowest similarity  from village Sibio-bio sampel A1 with A2 equal to 63,77%.   Key word : salacca, identification, morphological characters, descriptive method